Efficacy of polymer coating of probiotic beads suspended in pressurized and pasteurized longan juices on the exposure to simulated gastrointestinal environment - Chaikham P. (2014)
Alginate-coated Lactobacillus acidophilus LA5 or Lactobacillus casei 01 was recoated with either 0.1-0.5% (w/v) alginate or 0.05-0.15% (w/v) poly-L-lysine (PLL) plus 0.2% (w/v) alginate or 5-15% (w/v) gelatin, after which they were determined for survivability in gastric or bile longan juices. The morphology of encapsulated probiotic cells illustrated that recoated beads with 0.5% alginate showed a more compact surface and a greater protective effect than other recoating materials. The recoated beads with 0.5% alginate and 0.05-0.15% PLL plus 0.2% alginate of both strains showed the highest viability in gastric longan juice. In bile longan juice, only 0.5% alginate showed the best protection for both recoated beads. When considering the storage stability, encapsulated L. acidophilus LA5 exhibited a higher viable count than those of the free cells, whereas L. casei 01 showed equivalent viability of both free and double-coated cells. Based on the impact of pressurization or pasteurization, both processed juices gave rise to equivalent survivability of the probiotic cells during storage. © 2013 Informa UK Ltd. All rights reserved.